2013
DOI: 10.1155/2013/728529
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK Signaling in Pemphigus: Implications for Skin Autoimmunity

Abstract: p38 mitogen activated protein kinase (p38 MAPK) signaling plays a major role in the modulation of immune-mediated inflammatory responses and therefore has been linked with several autoimmune diseases. The extent of the involvement of p38 MAPK in the pathogenesis of autoimmune blistering diseases has started to emerge, but whether it pays a critical role is a matter of debate. The activity of p38 MAPK has been studied in great detail during the loss of keratinocyte cell-cell adhesions and the development of pem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 116 publications
0
31
0
1
Order By: Relevance
“…Indeed, signaling molecules such as, amongst a variety of others, PKC, RhoA, c-Myc and EGFR were demonstrated to participate in the pathogenesis of pemphigus (Spindler et al, 2013;Waschke, 2008;Waschke and Spindler, 2014). Especially, the phosphorylation of p38MAPK appears to be a central mechanism in pemphigus pathogenesis (Mavropoulos et al, 2013), because PV-IgG cause a rapid activation in cultured keratinocytes, mouse models and patients and inhibition of this kinase was protective both in vitro and in vivo (Berkowitz et al, 2008;Berkowitz et al, 2005;Berkowitz et al, 2006;Mao et al, 2014). Mechanistically, p38MAPK activation leads to reorganization of both the actin and intermediate cytoskeleton and to depletion of Dsg3 (Berkowitz et al, 2005;Jolly et al, 2010;Spindler et al, 2013), all of which are known hallmarks of pemphigus pathogenesis (Aoyama and Kitajima, 1999;Oktarina et al, 2011;Spindler et al, 2007;Spindler et al, 2011;Wilgram et al, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, signaling molecules such as, amongst a variety of others, PKC, RhoA, c-Myc and EGFR were demonstrated to participate in the pathogenesis of pemphigus (Spindler et al, 2013;Waschke, 2008;Waschke and Spindler, 2014). Especially, the phosphorylation of p38MAPK appears to be a central mechanism in pemphigus pathogenesis (Mavropoulos et al, 2013), because PV-IgG cause a rapid activation in cultured keratinocytes, mouse models and patients and inhibition of this kinase was protective both in vitro and in vivo (Berkowitz et al, 2008;Berkowitz et al, 2005;Berkowitz et al, 2006;Mao et al, 2014). Mechanistically, p38MAPK activation leads to reorganization of both the actin and intermediate cytoskeleton and to depletion of Dsg3 (Berkowitz et al, 2005;Jolly et al, 2010;Spindler et al, 2013), all of which are known hallmarks of pemphigus pathogenesis (Aoyama and Kitajima, 1999;Oktarina et al, 2011;Spindler et al, 2007;Spindler et al, 2011;Wilgram et al, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…For example, pemphigus vulgaris is a skin-blistering disease in humans, and enhanced phosphorylation of p38 MAPK is observed in pemphigus vulgaris skin. 51 Human keratinocytes treated with pemphigus vulgaris IgG showed p38 activation and retraction of KIF from the cell membrane. 5 The retraction of KIF was prevented by a p38 MAPK inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Acantholytic mechanisms involving autoantibody-antigen interaction have been reported to directly induce disruption of cell adhesion via intercellular signaling pathways, such as p38 mitogen activated protein kinase (MAPK), heat shock protein 27 (HSP 27), c-myc and epidermal growth factor (EGF)-extracellular signalregulated kinases (ERKs) 1/2 signals (Berkowitz et al, 2008;Getsios et al, 2009). Furthermore, a decrease in DSG-1 epidermal expression has been reported to interfere with DSC-1, keratin 10 and loricrin expression during skin differentiation (Getsios et al, 2009;Mavropoulos et al, 2013). It is known that KIFs retract in acantholytic keratinocytes, which, consequently, leads to the development of PF and pemphigus vulgaris (Bektas et al, 2013;Mavropoulos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a decrease in DSG-1 epidermal expression has been reported to interfere with DSC-1, keratin 10 and loricrin expression during skin differentiation (Getsios et al, 2009;Mavropoulos et al, 2013). It is known that KIFs retract in acantholytic keratinocytes, which, consequently, leads to the development of PF and pemphigus vulgaris (Bektas et al, 2013;Mavropoulos et al, 2013). Other studies have reported that DSC-1 is a potential auto-antigen in canine PF (Bizikova et al, 2011;; however, reduced DSC-1 expression was found in PE and PPP perhaps because it is possible that subtypes of superficial pemphigus share DSC-1 aberrance as well.…”
Section: Discussionmentioning
confidence: 99%